Microbial trophic interactions and mcrA gene expression in monitoring of anaerobic digesters - Alvarado, Alejandra; Montañez-Hernández, Lilia E.; Palacio-Molina, Sandra L.; Oropeza-Navarro, Ricardo; Luévanos-Escareño, Miriam P.; Balagurusamy, Nagamani (Frontiers in Microbiology, 2014)
Anaerobic digestion (AD) is a biological process where different trophic groups of microorganisms break down biodegradable organic materials in the absence of oxygen. A wide range of anaerobic digestion technologies is being used to convert livestock manure, municipal and industrial wastewaters, and solid organic wastes into biogas. AD gains importance not only because of its relevance in waste treatment but also because of the recovery of carbon in the form of methane, which is a renewable energy and is used to generate electricity and heat. Despite the advances on the engineering and design of new bioreactors for anaerobic digestion, the microbiology component always poses challenges. Microbiology of AD processes is complicated as the efficiency of the process depends on the interactions of various trophic groups involved. Due to the complex interdependence of microbial activities for the functionality of the anaerobic bioreactors, the genetic expression of mcrA, which encodes a key enzyme in methane formation, is proposed as a parameter to monitor the process performance in real time. This review evaluates the current knowledge on microbial groups, their interactions and their relationship to the performance of anaerobic biodigesters with a focus on using mcrA gene expression as a tool to monitor the process.